Transgender cinema - Bell-Metereau, Rebecca Louise (Quick takes., 2019)
"Transgender Cinema gives readers the big picture of how trans people have been depicted on screen. Beginning with a history of trans tropes in classic Hollywood cinema, from comic drag scenes in Chaplin's The Masquerader to Garbo's androgynous Queen Christina, and from psycho killer queers to The Rocky Horror Picture Show's outrageous queen, it examines a plethora of trans portrayals that subsequently emerged from varied media outlets, including documentary films, television serials, and world cinema. Along the way, it analyzes milestones in trans representation, like The Crying Game, Boys Don't Cry, Hedwig and the Angry Inch, and A Fantastic Woman. As it traces the evolution of trans people onscreen, Transgender Cinema also considers the ongoing controversies sparked by these movies and series both within LGBTQ communities and beyond. Ultimately it reveals how film and television have shaped not only how the general public sees trans people, but also how trans people see themselves."